Studying the effective of conductor polymer substrate on the electrical properties of semiconductors (Baghdad Science Journal, 2017)
This research includes depositionof thin film of semiconductor, CdSe by vaccum evaporation on conductor polymers substrate to the poly aniline where, the polymer deposition on the glass substrats by polymerization oxidation tests polymeric films and studied the structural and optical properties through it,s IR and UV-Vis , XRD addition to thin film CdSe, on of the glass substrate and on the substrate of polymer poly-aniline and when XRD tests was observed to improve the properties of synthetic tests as well as the semiconductor Hall effect proved to improve the electrical properties significantly